Melatonin Attenuates Chromium (VI)-Induced Spermatogonial Stem Cell/Progenitor Mitophagy by Restoration of METTL3-Mediated RNA N6-Methyladenosine Modification - Lv, Yinghua; Li, Tianjiao; Yang, Manman; Su, Lihong; Zhu, Zhendong; Zhao, Sihang; Zeng, Wenxian; Zheng, Yi (Frontiers in Cell and Developmental Biology, 2021)
Spermatogonial stem cells (SSCs) are the basis of spermatogenesis, and any damage to SSCs may result in spermatogenic disorder and male infertility. Chromium (VI) is a proven toxin, mutagen and carcinogen, perpetually detrimental to environmental organisms due to its intricate and enduring detoxification process in vivo. Despite this, the deleterious effects of Cr (VI) on SSCs and the underlying mechanisms remain poorly understood. In this study, we identified that Cr (VI) impaired male reproductive system in mouse testes and induced mitochondrial dynamic imbalance and mitophagy in SSCs/progenitors. Cr (VI) also downregulated the RNA N6-methyladenosine (m6A) modification levels in mitochondrial dynamic balance and mitophagy genes in SSCs/progenitors. Inspiringly, the toxic effects of Cr (VI) could be relieved by melatonin pretreatment. Melatonin alleviated Cr (VI)-induced damage to male reproductive system and autophagy in mouse testes. Melatonin also attenuated Cr (VI)-induced cell viability loss and ROS generation, as well as mitochondrial dynamic disorders and mitophagy in SSCs/progenitors. The protective roles of melatonin against Cr (VI)-induced mitophagy were exerted by restoration of METTL3-mediated RNA m6A modification and activation of mitochondrial fusion proteins MFN2 and OPA1, as well as inhibition of the mitophagy BNIP3/NIX receptor pathway. Thus, our study provides novel insights into the molecular mechanisms for RNA m6A modification underlying the gene regulatory network responsible for mitochondrial dynamic balance, and also lays new experimental groundwork for treatment of Cr (VI)-induced damage to male fertility.